2015
DOI: 10.1159/000368478
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Calcium, Magnesium and Parathyroid Hormone Induced by Hemodialysis with Citrate-Enriched Dialysis Solution

Abstract: Background/Aims: In recent years, one of technical attempts to improve biocompatibility and tolerability of the hemodialysis procedure is the substitution of acetate in dialysis solution with citrate. The aim of our study was to compare two dialysis solutions: traditional bicarbonate dialysis solution containing acetate (3 mmol/L) (solution A); and (solution C) commercially produced citrate-enriched bicarbonate dialysis solution (0.8 mmol/L citrate). Methods: Patients from a single hemodialysis center (N=126) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
3
15
0
4
Order By: Relevance
“…Previous reports also indicated that citrate reduced the levels of iCa at the end of the session [14,15]. In this study, we found that, paradoxically, serum iCa increased significantly after HD.…”
Section: Discussionsupporting
confidence: 66%
“…Previous reports also indicated that citrate reduced the levels of iCa at the end of the session [14,15]. In this study, we found that, paradoxically, serum iCa increased significantly after HD.…”
Section: Discussionsupporting
confidence: 66%
“…Associations between hypomagnesemia and an increased risk for type 2 DM, pre-DM, insulin resistance, obesity, dyslipidemia, hypertension and MS have been shown in various studies [21-29]. All of these conditions have a high incidence of hypomagnesemia as well as increased risk for cardiovascular mortality [24-26].…”
Section: Discussionmentioning
confidence: 99%
“…Citrate-based therapy was more effective on changes in serum calcium, magnesium and PTH [30], though more costly. Several observational studies have found that higher bicarbonate concentration may be associated with an improvement of kidney measures and survival for patients with CKD.…”
Section: Discussionmentioning
confidence: 99%